2021
DOI: 10.3390/ijms22158065
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Exosome Profile in ST-Elevation Myocardial Infarction Patients with and without Out-of-Hospital Cardiac Arrest

Abstract: The identification of new biomarkers allowing an early and more accurate characterization of patients with ST-segment elevation myocardial infarction (STEMI) is still needed, and exosomes represent an attractive diagnostic tool in this context. However, the characterization of their protein cargo in relation to cardiovascular clinical manifestation is still lacking. To this end, 35 STEMI patients (17 experiencing resuscitated out-of-hospital cardiac arrest (OHCA-STEMI) and 18 uncomplicated) and 32 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Plasma exosomes participate in the in ammatory immune response in acute myocardial infarction 20 . Acute myocardial infarction patients' protein expression in the blood is distinct from that of patients with SAP 21 . Exosomes of MSCs isolated from human umbilical cord blood have cardioprotective effects in animal models of AMI and cardiomyocyte hypoxia injury 22 , as reported by Marta Zarà et al 22 .…”
Section: Discussionmentioning
confidence: 92%
“…Plasma exosomes participate in the in ammatory immune response in acute myocardial infarction 20 . Acute myocardial infarction patients' protein expression in the blood is distinct from that of patients with SAP 21 . Exosomes of MSCs isolated from human umbilical cord blood have cardioprotective effects in animal models of AMI and cardiomyocyte hypoxia injury 22 , as reported by Marta Zarà et al 22 .…”
Section: Discussionmentioning
confidence: 92%
“…Secreted EVs are taken up by other cells, and cargo molecules have a wide range of functions in the recipient cells [ 8 ]. Among the cargos of EVs, microRNAs (miRNAs) have attracted attention as they are currently known to be involved in the development and progression of various diseases, such as cancer, cardiovascular disease, and metabolic disorders [ 9 , 10 , 11 ]. miRNAs are single-stranded non-coding RNAs consisting of around 22 bases; they regulate gene expression by inhibiting the translation or degradation of mRNAs that have sequences complementary to miRNAs in the 3’-untranslated region (3’-UTR) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mainly known for their central role in local/distant intercellular communication, the growing knowledge about sEVs has highlighted their potential as a rich source of biomarkers for several diseases [3,4]. We have recently shown that the number and size of plasma sEVs are higher in acute STEMI patients compared to chronic coronary syndrome (CCS) [5]. Moreover, STEMI sEVs are characterized by a greater expression of platelet markers [5], suggesting a critical role for platelet-derived sEVs in AMI.…”
Section: Introductionmentioning
confidence: 99%